2021
DOI: 10.3389/fmed.2021.652464
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Impact of COVID-19 on Human Gut Microbiome Research

Abstract: The coronavirus (COVID-19) pandemic has disrupted clinical trials globally, with unique implications for research into the human gut microbiome. In this mini-review, we explore the direct and indirect influences of the pandemic on the gut microbiome and how these can affect research and clinical trials. We explore the direct bidirectional relationships between the COVID-19 virus and the gut and lung microbiomes. We then consider the significant indirect effects of the pandemic, such as repeated lockdowns, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…The significant decline in infectious diseases caused by common respiratory pathobionts such as Streptococcus pneumoniae and Haemophilus influenzae , among others, reported in our geographical area [ 6 ], may also be associated to the impact of the lockdown on the nasopharyngeal microbiota. Nonetheless, given the complex interaction network between the microbiota and the host immune system, and the uncertainty of the long-term effects of COVID-19 on the human microbiota [ 34 ], we cannot be sure if these observed short-term alterations on the children’s nasopharyngeal microbiota development will have an impact on their health in the future and in which way.…”
Section: Discussionmentioning
confidence: 99%
“…The significant decline in infectious diseases caused by common respiratory pathobionts such as Streptococcus pneumoniae and Haemophilus influenzae , among others, reported in our geographical area [ 6 ], may also be associated to the impact of the lockdown on the nasopharyngeal microbiota. Nonetheless, given the complex interaction network between the microbiota and the host immune system, and the uncertainty of the long-term effects of COVID-19 on the human microbiota [ 34 ], we cannot be sure if these observed short-term alterations on the children’s nasopharyngeal microbiota development will have an impact on their health in the future and in which way.…”
Section: Discussionmentioning
confidence: 99%
“…Along with lung microbiota, the composition and diversity of gut microbiota are also altered in COVID-19 patients, suggesting a bidirectional association between the respiratory and GI tract microbiota [ 18 , 33 ]. The commensal microbiota ecosystem in the gut is complex and dynamic, and plays an important role in regulating the host immune system and metabolism [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Growing evidence suggests that SARS-CoV-2 has been detected not only in the respiratory system (nasopharyngeal and mid-nasal specimens) but also in the GI tract (stool and rectal swabs) of COVID-19 patients. Infection of gut epithelial cells by SARS-CoV-2 can disrupt the gut microbiome, inducing dysbiosis, intestinal inflammation, and gastrointestinal symptoms 18,19 . Moreover, recent studies have shown that COVID-19 is often associated with altered gut microbiota composition, reflecting disease severity [20][21][22][23] .…”
Section: Reviewmentioning
confidence: 99%
“…Disrupted gut microbiota can result in elevated levels of angiotensin-converting enzyme 2 (ACE2), due to epithelium breakdown and inflammation. ACE2 was reported to be a key target of the SARS-CoV-2 virus by triggering the inflammatory cascades (“cytokine storm”) known to worsen the severity of the COVID-19 disease [ 3 ]. The angiotensin converting enzyme (ACE) and its receptor (ACE2) play central roles in modulating the renin–angiotensin system (RAS).…”
Section: Introductionmentioning
confidence: 99%